Analysis of Unsignalized Intersection Performance on Jl. Dr Sutomo, Baturaja City - Samsul Bahri; Annisa Mawarda; Yuzuar Afrizal; Makmun Reza Razali; Gusta Gunawan (Universitas Bengkulu, 2026)
An unsignalized intersection is the meeting point of several road approaches without traffic signal control. The vehicle control mechanism is implemented through traffic signs and priority rules. Problems arise when traffic volume increases. Vehicles will cross each other, so conflicts between vehicles are becoming more frequent. The unsignalized intersection on Jl. Dr. Sutomo is a four-leg intersection with traffic flow levels that continue to increase. The purpose of this study is to analyze the performance of the unsignalized intersection using the method of The Indonesian Road Capacity Guidelines (PKJI) 2023. Data collection was carried out through field surveys for three days. Observations were conducted during peak hours, namely in the morning from 07:00 to 09:00 WIB, at midday from 12:00 to 14:00 WIB, and in the afternoon from 16:00 to 18:00 WIB. The results show that the unsignalized intersection on Jl. Dr. Sutomo, Baturaja City, has a capacity of 3446 passenger car unit (PCU)/hour. The highest traffic flow occurred on Monday at 08:30–08:45 WIB at 2932 PCU/hour with a degree of saturation of 0.85. Vehicles experienced a travel delay of 94.52 seconds/PCU and the vehicle queue probability ranged from 29% to 57%. This condition places the intersection at Level of Service C. Vehicles are dominated by higher traffic flows on the major road, with stable movements. There is an increase in internal movement friction, which causes traffic density to be at a moderate level. This condition makes drivers experience difficulty in increasing speed and overtaking each other. Keywords: unsignalized intersection, degree of saturation, delay